Accurate estimation of biomass production and partitioning efficiency in castor (Ricinus communis L.): ACCURATE ESTIMATION OF BIOMASS PRODUCTION AND PARTITIONING EFFICIENCY IN CASTOR - P LAKSHMAMMA; K ALIVELU; LAKSHMI PRAYAGA; C LAVANYA; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2017)
There is continuous leaf fall due to senescence from 35-60 days after sowing (DAS) till harvest depending on crop duration in castor which is not quantified in general for computation of total dry matter (TDM) and harvest index (HI). By calculating HI with the TDM at harvest of the plant which excludes senesced fallen leaf weight gives high HI values than actually are. In castor, major emphasisis on selecting genotypes with high partitioning efficiency which is shown by high HI. Hence, an experiment was conducted during 2013-15 for two years to devise suitable methodology for quantification ofsenesced fallen leaf while working out plant dry matter. Senesced fallen leaf was collected, quantified, factor for estimation of senesced leaf weight was developed using linear regression equation and model was validated. The equations derived for estimation of TDM and HI from senesced leaf include: TDM with senesced leaf weight = 1.217 * TDM without senesced leaf weight and HI with senesced leaf weight = 0.805* HI without senesced leaf weight. This factor can be used for accurate estimation of TDM at harvest and HI to enhance the quality of data for selection of genotypes with high partitioning efficiency.